Strengthening \(21^st\) Century Skills of Learners through Open and Distance Learning in Malaysia - Zulaihan Ismail; Raziana Che Aziz; Chiam Chooi Chea (Language, Literature and Education: Research Updates Vol. 3, 2025)
A dynamic, flexible and highly skilled workforce is needed in the twenty-first century to ensure economic growth can be sustained in an era of volatility, uncertainty, complexity and ambiguity. The education sector needs to play a key role in providing a workforce that meets the needs of the future in accordance with the digital transformation that is driving economic growth in the 21st century. Open and Distance Learning (ODL), as an alternative to traditional education, is seen as a platform to develop capable and adaptable individuals with strong values and skills that meet the demands of the 21st Century and beyond. Therefore, education that focuses on future readiness is needed in line with the needs of the 21st Century workforce. This study examines the importance of 21st Century skills in preparing future-ready learners in an ODL institution in Malaysia. This study uses descriptive methodology and purposive sampling techniques to collect primary data through structured questionnaires distributed to ODL learners. The findings indicate that 21st century skills have a significant impact on learners’ future readiness and are in line with the evolving demands of the 21st century workforce. The results of this study can provide insights to various stakeholders to design appropriate teaching and learning processes in ODL institutions to produce graduates who meet the future workforce, which will boost economic growth in Malaysia.